Pengaruh Minat Belajar dan Kemampuan Metakognitif Terhadap Hasil Belajar Matematika Siswa SMP Negeri 3 Lingsar - Andriyani, Ismi; Kurniati, Nani; Kertiyani, Ni Made Intan (Griya Journal of Mathematics Education and Application, 2025)
Students' mathematics learning outcomes are influenced by various factors, both internal and external. Two of the internal factors are learning interest and metacognitive ability. This study aims to determine the effect of learning interest and metacognitive ability on the mathematics learning outcomes of ninth grade students of SMP Negeri 3 Lingsar. This research uses a quantitative approach with associative research type and ex post facto design. The population of this study consisted of 106 ninth-grade students from SMP Negeri 3 Lingsar. The sampling technique was purposive sampling, which was 54 students from class IX A and IX B who were selected from 4 existing classes. Data collection using questionnaire and test methods. This research instrument is a questionnaire of interest in learning, a questionnaire of metacognitive abilities and a test of student math learning outcomes. The data analysis technique used is multiple linear regression. The results showed that interest in learning and metacognitive ability had a positive effect on the mathematics learning outcomes of SMP Negeri 3 Lingsar students by 98%.